Tales of justice and rituals of divine embodiment: oral narratives from the central Himalayas - Malik, Aditya (Oxford University Press, 2016)
Thinking about justice and being human -- God of justice -- Ideas of justice -- Writing intimacy -- Possession, alterity, modernity -- Transformations -- Dancers
Includes bibliographical references (pages 269-278) and index
Keywords: Kumaun Himalaya -- Religious life and customs; Volkserzählung; Religion; Kumauni; Gerechtigkeit; Mündliche Überlieferung; Kumaon